Depression in Home-Based Care: The Role of the Home Health Nurse. (July 2016) - Groh, Carla J.; Dumlao, Manuel S.
Abstract : Depression is a major health issue among older adults receiving home-based services yet is underdiagnosed and undertreated, which can result in negative health outcomes. Despite the recognized need for improved mental health services, significant gaps and barriers exist that contribute to less than optimal home-based depression management interventions. Home healthcare clinicians are well positioned to drive this effort for improving depression care with enhanced learning. Thus, the purpose of this article is to provide guidelines on improving depression care in homebound older adults based on four clinical functions central to home healthcare: screening, assessment, medication management, and patient/family education.